Suicide rates of migrants in United States immigration detention (2010-2020) - Parsa Erfani; Elizabeth T Chin; Caroline H Lee; Nishant Uppal; Katherine R Peeler (AIMS Press, 2021)
Objective: We determined the annual suicide rate of migrants detained by U.S. Immigration and Customs Enforcement (ICE) in the past decade. Methods: We performed a retrospective cohort analysis of the annual suicide rates for ICE detainees from federal fiscal years (FY) 2010-2020. Death date and cause of death were directly extracted from publicly available ICE Freedom of Information Act (FOIA) Library, ICE death reports, and ICE press releases. Annual suicide rates were calculated as suicides per 100,000 person-years and suicides per 100,000 admissions. Results: From 2010-2019, the mean number of suicides per 100,000 person-years was 3.3 (standard deviation (SD): 2.6). In 2020, the suicide rate increased 5.3 times the prior 10-year average to 17.4 suicides per 100,000 person-years. When calculating suicide rate based on admissions per FY, the mean number of suicides from 2010-2019 per 100,000 admissions was 0.3 (SD: 0.3). In 2020, the suicide rate increased 11.0 times the prior 10-year average to 3.4 suicides per 100,000 admissions. Conclusion: In 2020, the detainee suicide rate increased substantially compared to the past decade. This may point to a worsening mental health crisis in ICE detention.